UGMA POSTGRADUATE SYSTEM MANAGEMENT MODEL BASED ON BALANCED SCOREDCAR - Gómez, Fanny; GiI-Zambrano, José Luís (Cuadernos de Administración, 2007)
Th.is investigation airned to develop a management model based on balanced scorecard, to improve the quality and increase the postgraduate system performance, in the seven nucleus of the Gran Mariscal de Ayacucho (UGMA) uruversity. The investigation revealed that the PostgraduateUGMA doesn't have a performance management system that allows to evaluate the quality and effectiveness of the same. The research design is exploratory and field type. Questionnaires were applied to the sample formed of facilitators,administrative Staff and Graduate Students of the UGMA Nucleus to detennine performance levels of the postgraduate. The results show that the variables qua lit y and performance of the postgraduate are located in the average levels of 3.69 and 4.15, in the Likert scale of 1 to 5. The data obtained aUows to conclude that it is necessary to establish in the postgraduate a performance management model to continuously improve the same, with value added. We designed a performance management model based on the Balanced Scorecard approach, Which allows to translate the postgraduate strategy in operational terms in a continuous improvement process.